Influence of Buoyancy Module Characteristics on Free Vibration Response of Steep Wave Riser (SWR) - สุพบุตร สุพมิตร; คล้ายฉ่ำ การันต์ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
In the petroleum industry, subsea pipelines transporting crude oil from wellheads to production platforms are subjected to harsh environmental conditions and external forces that affect their structural integrity. High-stress concentrations often occur at the points where the pipeline touches the seabed, potentially leading to structural failure. To mitigate this issue, small buoyancy modules are strategically attached along sections of the pipeline to provide additional buoyant force, preventing direct contact with the seabed. The configuration of this riser system is called the “Steep Wave Riser (SWR)”. This paper aims to present a three-dimensional static and dynamic analysis of SWR pipelines using an elastic rod model, developed based on force and moment equilibrium principles. The model incorporates the effects of external forces, including hydrodynamic forces from water currents, hydrostatic pressure, buoyancy forces from the pipeline and floaters, self-weight, and internal fluid forces. The equilibrium equations are formulated in a Cartesian coordinate system and expressed as nonlinear differential equations, which are solved numerically using the Galerkin finite element method in conjunction with the NewtonRaphson iterative approach. Additionally, the free vibration characteristics of the SWR are analyzed using the eigenvalue problem-solving method to investigate the system’s dynamic behavior. Finally, the analysis focuses on optimizing the buoyancy module parameters to enhance the structural stability of SWR pipelines, minimize failure risks, and ensure efficient performance under complex subsea environmental conditions.